Disability on performing daily living activities in the elderly and history of falls: an analysis of the National Health Survey, 2013 - Adriano Drummond; Wendel Rodrigo Teixeira Pimentel; Valéria Pagotto; Ruth Losada de Menezes
ABSTRACT: Objective: The aim of this study was to verify the association between types of dependence for basic and instrumental activities of daily living and the occurrence of falls in the elderly. Methods: A cross-sectional, population-based study using data from 23,815 elderly people drawn from the National Health Survey (NHS) in 2013. The NHS, conducted by the Brazilian Institute of Geography and Statistics (IBGE) and the Ministry of Health, presents data collected in 81,767 households in more than 1,600 municipalities. The association between the independent variable (ADL disabilities) and the dependent variable (history of falls) was performed through multiple and crude analyses, regression. Results: There was a greater association between using the toilet and transfers (ABVD) and falls, and between shopping and taking care of finances (IADL) and falls. In addition, the association between Basic Activities of Daily Living and falls was greater for up to four activities, and the Instrumental Activities of Daily Living for up to three activities. Conclusion: Thus, the results obtained in the NHS reinforce the planning of preventive strategies considering the functional dependence.